The Role of the Regional National Crafts Council of East Nusa Tenggara Province in Empowering Woven Fabric Crafts Groups - BETI, Fince Orita; PANDIE, David B.W; KELEN, Pius Bumi (PT Batara Swastika Harati, 2024)
This research aims to determine the role of the NTT Dekranasda in empowering woven fabric craft groups. This research uses a qualitative descriptive method with combined data collection techniques through interviews, observation, documentation and focus group discussions (FGD). The results of the research show that Dekranasda NTT has played a role in empowering woven fabric craft groups, including Dekranasda NTT acting as a motivator in human development and institutional development, a communicator in business development and institutional development, and a dynamist in business development and institutional development. However, in carrying out its role, Dekranasda NTT experienced several obstacles, including limited capital to carry out woven fabric craft development activities again and obstacles faced by craft groups, namely lack of capital and raw materials in the weaving process, resulting in delays in every activity. Craft groups still need to issue business permits and copyrights for each of their businesses and weavings; this could be a waste of money for anyone who is not responsible for plagiarizing the weaving that the craft group has weaved.